The Effects of Gemar Booklet Media on the Level of Knowledge and Behavior of Mothers in Giving MP-ASI (Complementary food) for 6-12 Months Infants in Arcawinangun - Shaulla Salsabila; Ulfa Azizah (Proceedings Series on Health & Medical Sciences, 2024)
Background: MP-ASI is a transitional food given when babies are six months old to minimize the risk of malnutrition. One of the success factors in giving MP-ASI is the mother's knowledge regarding the accuracy of the baby's age and the composition contained therein. Food composition, food texture, and frequency of feeding are crucial in the practice of complementary feeding, and in this modern era, mothers still underestimate them. Method: This study used a quantitative method, with a quasi-experimental design with one group pre and post-test. The sample of this research was 46 respondents with a purposive sampling technique. Data analysis used the Wilcoxon Signed Rank Test. Results: The level of knowledge of the intervention group before and after the intervention was given had an average of 6.85 (enough) to 11.83 (good). The behaviour level of the intervention group before and after the intervention had an average of 40.59 (incorrect) to 48.91 (accurate). The p-value of the Wilcoxon Signed Rank Test (0.00) means that booklet media affects the level of knowledge and behaviour. Conclusion: The GEMAR booklet media is influential in efforts to increase the level of knowledge and behaviour of mothers in giving MP-ASI to infants aged 6-12 months.